2018
DOI: 10.1007/s10661-018-6675-6
|View full text |Cite
|
Sign up to set email alerts
|

Performance of biotic indices in comparison to chemical-based Water Quality Index (WQI) in evaluating the water quality of urban river

Abstract: In order to evaluate the water quality of one of the most polluted urban river in Malaysia, the Penchala River, performance of eight biotic indices, Biomonitoring Working Party (BMWP), BMWP, BMWP, Average Score Per Taxon (ASPT), ASPT, BMWP, Family Biotic Index (FBI), and Singapore Biotic Index (SingScore), was compared. The water quality categorization based on these biotic indices was then compared with the categorization of Malaysian Water Quality Index (WQI) derived from measurements of six water physicoche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 41 publications
1
8
0
1
Order By: Relevance
“…The freshwater macroinvertebrate taxa vary in response to organic pollution; and thus, their diversity and composition have been used to make inferences about pollution loads (Kenney et al, 2009;Wan Abdul Ghani et al, 2018;Tampo et al, 2020). Generally, in natural pristine rivers, high abundances and richness of species could be found (Barbour et al, 1996(Barbour et al, , 1999.…”
Section: Introductionmentioning
confidence: 99%
“…The freshwater macroinvertebrate taxa vary in response to organic pollution; and thus, their diversity and composition have been used to make inferences about pollution loads (Kenney et al, 2009;Wan Abdul Ghani et al, 2018;Tampo et al, 2020). Generally, in natural pristine rivers, high abundances and richness of species could be found (Barbour et al, 1996(Barbour et al, , 1999.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of the COD levels, the Student's test results indicated that measured levels were significantly lower ( t > 10, df = 4, p < 0.0005) than the reference COD of 40.00 ± 00 mg/L across all 17 SPs, except SP5 with no significant differences ( t < 1, df = 4, p > 1.00) (Supporting Information: Table ). Interestingly, the lower BOD and COD levels indicated reduced aerobic and oxidation activities in watercourses (Cota et al, 2002; Wan Abdul Ghani et al, 2018), which could be considered indicative of good water quality. The ANOVA results among all SPs showed highly significant differences among the measured COD levels ( F 16,34 = 68.75, p < 2.20 × 10 −16 ).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the Biological Monitoring Working Party (BMWP) index was developed to determine the degree of pollution in aquatic systems (Herman & Nejadhashemi, 2015; Roldán, 2003). The BMWP index relates the presence of pollution‐tolerant macroinvertebrates, identified at the family level, to the water‐quality parameters, and organic or inorganic pollutants (Herman & Nejadhashemi, 2015; Roldán, 2003; Wan Abdul Ghani et al, 2018). Examples of organic pollutants associated with degraded aquatic environments as determined by tolerant macroinvertebrates include hospital sewage, domestic and animal waste (e.g., tilapia farms), agriculture residues, and algae detritus (Cabrera et al, 2021; Cota et al, 2002; Roche et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Nosso estudo também apontou distintos grupos que se caracterizam pelas condições da qualidade físico-química e microbiológica da água, onde o grupo com pontos fora da área urbana (G1) assinalaram relações diretas com baixa DBO5,20, CE, STD, NO3, Cle COL TERM (COMPANHIA DE TECNOLOGIA DE SANEAMENTO AMBIENTAL, 2006;MENEZES et al, 2016;DANELUZZI;GONÇALVES;FREITAS, 2018;OLIVEIRA;OLIVEIRA;LIMA, 2018). Esta é uma característica relatada por outros estudos na Amazônia (VITAL, 2004;MELLO;SANTOS, 2018;PIMENTEL et al 2019), e por estudos internacionais em rios urbanos na China, Japão (HUANG et al, 2010;FENG et al, 2018;WAN ABDUL GHANI et al, 2018), advertindo que altos índices destas variáveis são fortes indicadores de atividades antrópicas urbanas.…”
Section: Discussionunclassified